2018
DOI: 10.1108/ijrdm-10-2017-0245
|View full text |Cite
|
Sign up to set email alerts
|

Determinants, transactional alignment, and performance outcomes of franchise contract length

Abstract: Purpose The purpose of this paper is to explore the determinants, transactional alignment and performance outcomes of franchise contract length using transaction costs theory (TCT) and resource-based theory (RBT). Design/methodology/approach The author hypothesizes that franchisors choose contract length according to TCT and RBT arguments. TCT explains the safeguarding function of contracts: the franchisors will offer longer contracts when franchisees’ specific investments are high and environmental uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In other words, this contract characteristic reflects the time scope for which the franchisor and franchisee commit to their relationship (even though premature contract terminations and contract extensions are possible; Lafontaine and Shaw 1999). Previous research on the role of contract duration in franchising partnerships suggests that a longer contract duration enhances performance in terms of growth and profitability through lowered coordination and control costs (Gorovaia 2019). In addition to lower transaction costs, long-lasting contracts promote commitment and interorganizational learning, enabling both parties to develop relational strategic assets and leverage knowledge more efficiently (Gorovaia and Windsperger 2018).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In other words, this contract characteristic reflects the time scope for which the franchisor and franchisee commit to their relationship (even though premature contract terminations and contract extensions are possible; Lafontaine and Shaw 1999). Previous research on the role of contract duration in franchising partnerships suggests that a longer contract duration enhances performance in terms of growth and profitability through lowered coordination and control costs (Gorovaia 2019). In addition to lower transaction costs, long-lasting contracts promote commitment and interorganizational learning, enabling both parties to develop relational strategic assets and leverage knowledge more efficiently (Gorovaia and Windsperger 2018).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The RBV is a theoretical perspective accepted widely in retail management and used in research on various aspects, including product knowledge (McGuinness and Hutchinson, 2013), franchise effectiveness (Gorovaia, 2019), omnichannel retail resources and capabilities (Mrutzek-Hartmann et al, 2022), and retail performance (Kim et al, 2022). RBV asserts that a firm's competitive advantage lies in its unique resources, which are valuable, inimitable and non-substitutable (Barney, 1991).…”
Section: Literature Review 21 Theoretical Framework: Resource-based A...mentioning
confidence: 99%
“…Also, the optimal proportion between company-owned and franchised units has been shown as sector dependent (Barth elemy, 2008;Srinivasan, 2006;Yin and Zajac, 2004) but no research has studied how the industry determine the level of plurality within a system. IJRDM 51,6 5.10 Strategic variables Combs et al (2004) identified three strategic groups among franchise chains based on their managerial expertise, capital scarcity, monitoring costs/local market knowledge needs, agency cots and expansion (Gorovaia, 2019;Peris-Ortiz et al, 2012;Piot-Lepetit et al, 2014). They observed that chains which are influenced to franchise due to resource-scarcity perform worse than those that choose the ratio of franchised units based on monitoring cost considerations.…”
Section: Industry Variablesmentioning
confidence: 99%
“…Combs et al. (2004) identified three strategic groups among franchise chains based on their managerial expertise, capital scarcity, monitoring costs/local market knowledge needs, agency cots and expansion (Gorovaia, 2019; Peris-Ortiz et al. , 2012; Piot-Lepetit et al.…”
Section: Impact Consistency Of Franchise Success Determinantsmentioning
confidence: 99%